OPEN-AIR SUN DRYING IN THRACE REGION OF GREECE: THE EXPERIMENTAL INVESTIGATION OF THYME AND MINT LEAVES - Ismail, O.; Beyribey, B. (PLAPIQUI(UNS-CONICET), 2013)
In this work, open-air sun drying of thyme (Thymus Vulgaris) and mint (Mentha Spicata)leaves was investigated. A falling rate period was occurred in drying thyme and mint leaves, starting from the initial moisture content (%73.80 for thyme and %84.70 for mint) to the final moisture content (%7.6 for thyme and %4.85 for mint). Drying times were obtained as 440 for thyme and 420 minutes for mint. L values of fresh and dried herbs were respectively found as 40.25 and 35.70 for thyme and as 44.01 and 33.08 for mint. The effective diffusivities were determined as 2.2571*10(-10) m(2)s(-1) for thyme and as 1.2768*10(-10) m(2)s(-1) for mint.
Keywords: Open-air sun drying; Thyme; Mint; Effective diffusivity; ESSENTIAL OIL; OXIDATIVE STRESS; MINCED BEEF; VULGARIS L.; HOT AIR; KINETICS; EXTRACTS; COMBINATION; COLOR; NISIN; Engineering